Impacts of chlorine chemistry and anthropogenic emissions on secondary pollutants in the Yangtze river delta region. (15th October 2021) - Li, Jingyi; Zhang, Na; Wang, Peng; Choi, Minsu; Ying, Qi; Guo, Song; Lu, Keding; Qiu, Xionghui; Wang, Shuxiao; Hu, Min; Zhang, Yuanhang; Hu, Jianlin
Abstract: Multiphase chemistry of chlorine is coupled into a 3D regional air quality model (CMAQv5.0.1) to investigate the impacts on the atmospheric oxidation capacity, ozone (O3 ), as well as fine particulate matter (PM2.5 ) and its major components over the Yangtze River Delta (YRD) region. The developed model has significantly improved the simulated hydrochloric acid (HCl), particulate chloride (PCl), and hydroxyl (OH) and hydroperoxyl (HO2 ) radicals. O3 is enhanced in the high chlorine emission regions by up to 4% and depleted in the rest of the region. PM2.5 is enhanced by 2–6%, mostly due to the increases in PCl, ammonium, organic aerosols, and sulfate. Nitrate exhibits inhomogeneous variations, by up to 8% increase in Shanghai and 2–5% decrease in most of the domain. Radicals show different responses to the inclusion of the multiphase chlorine chemistry during the daytime and nighttime. Both OH and HO2 are increased throughout the day, while nitrate radicals (NO3 ) and organic peroxy radicals (RO2 ) show an opposite pattern during the daytime and nighttime. Higher HCl and PCl emissions can further enhance the atmospheric oxidation capacity, O3, and PM2.5 . Therefore, the anthropogenic chlorine emission inventory must be carefully evaluated and constrained. Graphical abstract: Image 1 Highlights: Anthropogenic chlorine enhances O3 and PM2.5 in the Yangtze River Delta region by up to 4% and 6%, respectively. Changes in the secondary pollutants were due to changes in the HO x and RO2 radicals during the day and NO3 radical at night. Anthropogenic chlorine emissions were underestimated by a factor of 10 based on the observations in Taizhou.